(untitled) (Global Journal of Science Frontier Research, 2017)
Hydrological analysis and performance of watershed depends on the geo-Morphometric individuality of basin. Watershed prioritization for the present study is done via Morphometric analysis. Prioritization of 22 sub-watersheds of Alaknanda basin is done using linear, areal and dimensionless aspects. Sub-watersheds are delineated using ArcGIS as per DEM. Evaluation of drainages and other comparative parameters such as stream order, stream length ratio, stream frequency, form factor, drainage texture, drainage density, elongation ratio, circulatory ratio, compactness constant and bifurcation ratio has been independently calculated for each sub-watershed using remote sensing & GIS techniques. Stream order upto 7 th order has been analyzed & study area is divided into 22 sub-watersheds namely SW-1, SW-2 and so on till SW-22. Based on the examination, watersheds are divided into nine categories namely Extremely Very High, Extremely High, Very High, High, Medium, Low, Very Low, Extremely Low & Extremely Very Low in expressions of priority for conservation & preservation of natural resources.